Nonlinear Finite Element Analysis of Reinforced Concrete Cylindrical Shells - A.M.Jawad, David (Basrah Journal for Engineering Sciences, 2015)
The study investigates the behavior of reinforced concrete cylindrical shells under monotonically increasing loads. Three-dimensional models of six small-scale experimental shells with length-to-radius ratios ranging from short (0.84) to long (5.0) are implemented within the context of the finite element method, through use of the ANSYS computer code, and the nonlinear response is traced throughout the entire load range up to failure. Cracking occurs at working load levels, with subsequent reduction in shell stiffness. Increasing loads lead to failure modes varying from a beam failure in long shells, combined longitudinal and transverse cracking in intermediate length shells, and abrupt diagonal with limited transverse cracking in short shells. Ultimate load capacities range from 5.0 kPa to 60.0 kPa increasing with decreasing length-to-radius ratios.